Studies on pollen viability in Jasminum spp. - S, PAVITHRA; V, DHANANJAYA M; NAIR, SUJATHA A; KUMAR, RAJIV; S, YOGEESHA H; M, MUNIKRISHNAPPA P; V, DEVAPPA; K, HALESH G; A, KALAIYARASI (The Indian Journal of Agricultural Sciences, 2018)
In vitro studies on pollen viability of six jasmine species, viz. Jasminum sambac, J. auriculatum, J. grandiflorum, J. multiflorum, J. flexile and J. malabaricum, was conducted at ICAR-Indian Institute of Horticultural Research, Hesaraghatta Lake Post, Bengaluru during 2016-17. Results revealed that species Jasminum malabaricum recorded highest pollen viability (96.57%) as well as pollen germination (91.58%) followed by J. flexile (84.92% and 81.86%, respectively) and J. auriculatum (71.32% and 71.08%, respectively) under in vitro condition. The species J. sambac significantly recorded lowest pollen viability (34.27%) and germination (34.09%). Significantly highest normal shaped pollen grains were observed in J. auriculatum (96.92%) which was at par with J. malabaricum (96.89%) and J. grandiflorum (93.63%). Modified BK germination medium containing 100 ppm H3BO3 + 300 ppm Ca(No3)2 + 200 ppm MgSO4) with 10% sucrose + 15% PEG 4000 solution was found optimal for highest in vitro germination in J. malabaricum (91.58%). However, maximum length of pollen tube was recorded in J. flexile (1170.68 Î¼m) followed by J. malabaricum (951.11 Î¼m). The viable pollen diameter of different species ranged from 38.25 Î¼m (J. auriculatum) to 46.53 Î¼m (J. malabaricum). Pollen grains collected during evening (05:00 pm to 06:00 pm) at the time of anthesis showed best results. Pollen tubes revealed abnormalities such as bulging and coiling of tips in J. sambac and J. grandiflorum. This might be one of the reasons for no fruit set when J. sambac used as pollen parent. From this in vitro pollen germination study, species J. malabaricum, J. flexile and J. auriculatum were identified as most suitable male parents compared to other species.